Telaaah Kritis Pasal 28 Kompilasi Hukum Islam Perspektif Keadilan Gender Dalam Perkawinan - Jhon Alwi Situngkir (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The Compilation of Islamic Law consists of three books, namely book I on marriage, book II on inheritance, book III on endowments explained in Article 83. The Compilation of Islamic Law requires wives to organize household affairs is discrimination against gender, domestication of women causes unproductivity and marginalization of women from their essence as human beings. Fulfillment of political, economic, citizenship, education rights, and roles in the household must be fulfilled. And the division of husband and wife roles in the public and domestic environments is carried out through deliberation which leads to gender role justice. Gender justice in the household can be realized as long as men (husbands) can treat their wives and children fairly.